2023
DOI: 10.3389/fcvm.2023.1153310
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with lipid control in outpatients with heart failure

Abstract: BackgroundDyslipidemia is common among patients with heart failure, and it negatively impacts clinical outcomes. Limited data regarding the factors associated with poor lipid control in patients with HF patients. Therefore, this study aimed to evaluate lipid control and to explore the factors associated with poor lipid control in patients with HF.MethodsThe current cross-sectional study was conducted at outpatient cardiology clinics at two major hospitals in Jordan. Variables including socio-demographics, biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…Another argument with our study to age is food choices in seniors, where consuming meat and its products and alcoholic beverages has been common among adults in some countries; we considered this a cause of abnormal LDL-C levels among our patients (Figure 4.a). A recent study on heart failure revealed that the participants' mean age was 63±12 years, and approximately 88.1% were not physically active [42]. Similarly, a study carried out in Cameroon reported a mean age of 61 years, with a common age of 50-60 years; however, this study contradicted our findings on lipid abnormalities because it reported a high occurrence of abnormal TG levels among individuals with cardiovascular risk and disease [43].…”
Section: Association Of Lipid Profile Abnormalities and Cvdscontrasting
confidence: 98%
“…Another argument with our study to age is food choices in seniors, where consuming meat and its products and alcoholic beverages has been common among adults in some countries; we considered this a cause of abnormal LDL-C levels among our patients (Figure 4.a). A recent study on heart failure revealed that the participants' mean age was 63±12 years, and approximately 88.1% were not physically active [42]. Similarly, a study carried out in Cameroon reported a mean age of 61 years, with a common age of 50-60 years; however, this study contradicted our findings on lipid abnormalities because it reported a high occurrence of abnormal TG levels among individuals with cardiovascular risk and disease [43].…”
Section: Association Of Lipid Profile Abnormalities and Cvdscontrasting
confidence: 98%